Exploring self-care needs of pregnant women with gingivitis: A qualitative study in Iran - Babak Nemat-Shahrbabaki; Arezoo Fallahi; Sina Valiee; Mozhdeh Zarei; Parisa Fallahi (Wolters Kluwer Medknow Publications, 2018)
Background: Oral self-care behaviors are not satisfactory among pregnant women; incidence of gingivitis is high in them and training programs have slightly improved their gingivitis. This study was aimed to explore self-care needs of pregnant women suffering from gingival inflammation. Materials and Methods: This study was carried out in Sanandaj, west of Iran, in 2017. Twenty pregnant women with gingivitis were included in the study. Data were collected via semi-structured individual and group interviews and note-taking, and were analyzed by conventional content analysis. To confirm the accuracy and strength of the data, credibility, confirmability, and transferability components were taken into account. Results: The results of data analysis yielded six major categories, including "organizational support," "dentist's professional competence," "increasing perceived threat," "increasing self-efficacy," "increasing perceived benefits," and "culture-making." Increased self-efficacy was the most important concern of pregnant women. Conclusions: The findings showed that self-care behaviors to prevent gingivitis in pregnant women are influenced by various factors. It is essential to consider the cooperation of the media and organizations, support of society, and attention of families and authorities to oral health education and disease prevention among women.